Facile synthesis of laminated porous WS2/C composite and its electrocatalysis for oxygen reduction reaction. (26th April 2018) - Huang, Huodi; Zhang, Xiaofeng; Zhang, Yi; Huang, Baohua; Cai, Jiannan; Lin, Shen
Abstract: The Vulcan XC-72R modified WS2 nanocomposite (WS2 /C）was prepared by solid reaction process combined with sonication. The as-prepared WS2 /C nanocomposite presents a laminated porous structure by SEM and TEM characterization. The electrochemical experiments show that the onset potential and the limiting-current density of WS2 /C is 0.78 V and 4.99 mA cm −2, respectively, which is much higher than, WS2 (3.12 mA cm −2 ) and Vulcan XC-72R (2.79 mA cm −2 ). The number of transfer electrons in ORR at the WS2 /C nanocomposite electrode is 3.70, which is close to four-electron process. Besides, the current density of WS2 /C nanocomposites remained at 90% after 20, 000 s, indicating its superior electrochemical stability. All these facts reveal that the as-prepared WS2 /C nanocomposite can be regarded as a promising cathode ORR catalyst for fuel cell. Highlights: The laminated porous WS2 /C composites were prepared by a solid-state reaction process. The composite exhibits a high specific surface area. The composite shows improved catalytic activity and superior stability for ORR.